Strategi Pemasaran UD. Semangat Dalam Memasarkan Kuliner Jajanan Khas Lombok Di Desa Jatisela Lombok Barat - Aini, Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The marketing factor didn't go well at UD. Excited because the support is still low. The objectives of this study are 1) To find out the marketing dimensions of traditional snacks in Jatisela Village 2) To find out what facilities and infrastructure are still hampering marketing development. 3) Marketing strategies that have not used a digital marketing system. The research is located in Jatisela Village, Gunungsari District, West Lombok Regency. Regarding producing culinary snacks typical of the Lombok region, the method used in this study is a qualitative data approach with qualitative descriptive analysis techniques, data collection through literature studies, direct observation or documentation. Data analysis uses interactive qualitative, namely data reduction, data display and conclusion drawing and data triangulation. This research will bring changes to the improvement of marketing strategy at UD.Semangat